REFLECTION GOOD NAME AND CORRUPTION BEHAVIOR IN INDONESIA FROM PROVERBS 22:1 - Ester Agustini Tandana (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2023)
This study investigates the relationship between maintaining a good name and the prevalence of corruption behavior in Indonesia. By conducting an exegetical analysis of Proverbs 22:1, which emphasizes the value of a good name, the research explores its relevance to the issue of corruption in the Indonesian context. The research explores the socio-cultural significance of a good name in Indonesian society and its impact on individual and collective behavior. It examines the perception of integrity and the role of reputation in shaping ethical conduct among public officials, business leaders, and citizens. The study also reviews existing literature, case studies, and empirical evidence related to corruption in Indonesia. Drawing insights from Proverbs 22:1, which states that